KAJIAN PENGEMBANGAN STRATEGI POTENSIAL INDUSTRI TEPUNG TAPIOKA RAKYAT (ITTARA) DI KABUPATEN LAMPUNG TIMUR [A Study of Potential Strategy Development on Small Scale Tapioca Industry (ITTARA) in East Lampung District] - Muhadi Muhadi (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2017)
The objective of this research was to find out the weakness and the strength of ITTARA located in East Lampung, as a basis to develop the potential strategy of ITTARA so that it could be sustainable and economically improved. Analysis methods used were the SWOT analysis (strength, weakness, opportunity, and threat) and Analytical Hierarchy Process (AHP), while the potential strategy concept was adapted from existing ITTARA conditions. The SWOT analysis showed that there was weakness aspect that dominated the strength aspect in internal factor of ITTARA, nevertheles there was opportunity from external factor that could be optimized. These strategies should be developed were diversifying final product, conducting side business of by product, and improving technology use, as well as efficiency of production cost. These business strategy improvements were then analyzed using AHP to choose one strategy by using criteria of market potential, production cost, product added value, technology and competitor. The result showed the most potential to be developed was improving tehcnology use by conducting the two times milling tapioca production. Keywords: AHP, ITTARA, SWOT analysis, two times milling